Lennon, Dylan, Alice, & Jesus : the spiritual biography of rock and roll - Laurie, Greg; Terrill, Marshall (Salem Books an imprint of Regnery Publishing, 2022)
"Love 'em or hate 'em, there is little denying that rock stars have a special gift from God to do what they do. But where there is great anointing, there is also great warfare. How have these artists learned to relate to the God who gave them their gift? As you'll see, not all of them have. Some of them got rolled by rock, falling prey to addiction, excess, and early death. But others came to fall on the Rock of Ages, and found their souls along the way" -- inside flap.